Nghiên cứu sự tương tác giữa cacboplatin với guanine bằng phương pháp tính toán hóa học lượng tử - Thu An, Nguyễn Thị; Nhật, Phạm Vũ (Vietnam Journal of Chemistry, 2017)
carboplatin and the purine base site of DNA using guanine as a model reactant. Thermodynamic parameters, electronic structures, bonding characteristics and spectroscopic properties of the resulting complexes are investigated in the framework of density functional theory (B3LYP functional) along with correlation consistent basis sets. The computed results show that these interactions are dominated by electrostatic effects, namely the H-bond contributions, and there exists a charge flow from H atoms of ligands to O atoms of carboplatin when the hydrogen bond was formed. Keywords. Anticancer, cisplatin, carboplatin, DFT, NBO charge.